A 22-year experience with pancreatic resection for metastatic renal cell carcinoma. Issue 2 (February 2020) - Anderson, Blaire; Williams, Gregory A.; Sanford, Dominic E.; Liu, Jingxia; Dageforde, Leigh A.; Hammill, Chet W.; Fields, Ryan C.; Hawkins, William G.; Strasberg, Steven M.; Doyle, Majella B.; Chapman, William C.; Khan, Adeel S.
Abstract: Background: The pancreas is a rare site of metastases, although metastatic renal cell carcinoma (mRCC) is the most commonly reported secondary tumor. Pancreatectomy has been described in selected patients with localized metastases, but long-term benefit remains poorly defined. Methods: A retrospective review of a prospectively maintained database was performed to evaluate the outcomes of patients undergoing pancreatectomy for mRCC at a tertiary care center from 1995–2017. Postoperative complications were evaluated using the Modified Accordion Grading System (MAGS) and Kaplan–Meier curves and log-rank tests were utilized for survival analysis. Results: 29 patients underwent pancreatectomy for mRCC including 15 distal pancreatectomies (DP), 10 pancreaticoduodenectomies (PD) and 4 total-pancreatectomies (TP). The mean age was 67 ± 8 years, and 15 were male. The median time from index nephrectomy to pancreatectomy was 8 (IQR: 3.72–12.2) years. There was no 90 Day post-pancreatectomy mortalities and the morbidity incidence included 13 Minor MAGS and 8 Severe MAGS complications respectively. Post-pancreatectomy disease specific survival at 2- and 4-years were 89% and 80% with 12 patients being alive at last follow up. Conclusions: Pancreatic resection can be safely performed in select patients with localized mRCC with favorable long-term outcomes.